2010
DOI: 10.1016/j.paid.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The General Factor of Personality and its relation to Self-Esteem in 628,640 Internet respondents

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 15 publications
1
53
1
Order By: Relevance
“…The relationship between personality and selfesteem in this study is consistent with previous studies (Erdle et al, 2010;Orth, Trzesniewski, & Robins, 2010;Robins, Tracy et al, 2001;Shackelford & Michalski, 2011). Results showed that agreeableness, conscientiousness, emotional stability and openness positively correlate with self-esteem and are negatively correlated with neuroticism (Graziano & Ward, 1992;Watson et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relationship between personality and selfesteem in this study is consistent with previous studies (Erdle et al, 2010;Orth, Trzesniewski, & Robins, 2010;Robins, Tracy et al, 2001;Shackelford & Michalski, 2011). Results showed that agreeableness, conscientiousness, emotional stability and openness positively correlate with self-esteem and are negatively correlated with neuroticism (Graziano & Ward, 1992;Watson et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…They found that the social problem-solving (especially with negative problem orientation) appears to act as a mediator in the relationship between self-esteem and aggression. In the literature the relationship between the Big Five personality dimensions and self-esteem was studied (Erdle, Irwing, Rushton & Park, 2010;Robins, Tracy et al, 2001;Shackelford & Michalski, 2011). Results showed that agreeableness, conscientiousness, emotional stability and openness correlate positively with self-esteem (Graziano & Ward, 1992;Watson, Suls & Haig, 2002).…”
mentioning
confidence: 99%
“…The nonclinical inventories include the Big Five and Big Five alternatives, the California Psychological Inventory, the Comrey Personality Scales, the EAS Temperament Scales, the Eysenck Personality Questionnaire, the Guilford-Zimmerman Temperament Survey, the Hexaco Personality Inventory, the Hogan Personality Inventory, the Jackson Personality Inventory, the Multidimensional Personality Questionnaire, the Personality Research Form, the Temperament and Character Inventory, and the Trait Emotional Intelligence Questionnaire (Erdle, Irwing, Rushton, & Park, 2010;Figueredo, Vásquez, Brumbach, & Schneider, 2004;Loehlin & Martin, 2011;Musek, 2007;Rushton et al, 2008;Rushton, Bons, Ando, Hur, Irwing,, Vernon, Petrides, & Barbaranelli;2009;Rushton & Irwing, 2008, 2009c, 2009dSchermer & Vernon, 2010;Veselka, Schermer, Petrides, & Vernon, 2009a;Veselka, Schermer, Petrides, Cherkas, Spence, & Vernon, 2009b;Zawadzki & Strelau, 2010).…”
Section: Are G and The General Factor Of Personality (Gfp) Correlatedmentioning
confidence: 99%
“…The largest study to find a GFP comprised a sample of 628,640 Internet respondents who completed the Big Five Inventory (Erdle et al, 2010). One study found the GFP was independent of method variance using a multitrait-multimethod analysis of self-, teacher-, and parent-ratings of 391 13-to 14-year-olds on the Big Five Questionnaire-Children (Rushton et al, 2009).…”
Section: Are G and The General Factor Of Personality (Gfp) Correlatedmentioning
confidence: 99%
“…However, Erdle et al (2009) had already used Anusic et al's largest data set, now doubled in size (628,423 vs. 326,641 Internet respondents), and found that when Self-Esteem was partialed out, the Big Two continued to emerge. Subsequently, Erdle et al (2010) extracted the GFP from the Big Two in this same sample and identified self-esteem as a constituent part of the GFP, thereby replicating Musek's (2007) observation that the GFP is related to self-esteem and positive affect.…”
mentioning
confidence: 94%